Status and factors associated with patient activation and its relationship with HIV clinic outcomes among Yi minority people living with HIV in Liangshan, China: a cross-sectional study - An, Wenhong; Tang, Xuefeng; Xiao, Xueling; Aku, Waha; Wang, Honghong (Frontiers in Public Health, 2023)
Objectives: This study aimed to explore the status and factors associated with patient activation among Yi minority PLWH in Liangshan, China and to determine whether patient activation is associated with HIV clinic outcomes. Methods: This cross-sectional study included 403 Yi minority people living with HIV (PLWH) in Liangshan between September and October 2021. All participants completed an anonymous survey measuring sociodemographic characteristics, HIV-related information, patient activation and illness perception. Multivariate linear regression and multivariate binary logistic regression were used to explore factors associated with patient activation and the association between patient activation and HIV outcomes, respectively. Results: The Patient Activation Measure (PAM) score was low (mean = 29.8, standard deviation = 4.1). Participants with negative illness perception, low income, and self-rated antiretroviral therapy (ART) effect based on self-perception were most likely to have a lower PAM score (β = -0.3, -0.2, -0.1, respectively; all P < 0.05); those with having disease knowledge learning experiences and an HIV-positive spouse were more likely to have a higher PAM score (β = 0.2, 0.2, respectively; both P < 0.001). A higher PAM score (AOR = 1.0, 95% CI: 0.9, 1.0) was associated with viral suppression, mediated by gender (AOR = 2.3, 95% CI: 1.4, 3.7). Conclusion: Low patient activation level among Yi minority PLWH impacts HIV care. Our findings indicate patient activation is associated with viral suppression for minority PLWH in low- and middle-income settings, suggesting that tailored interventions enhancing patient activation may improve viral suppression.